Analisis metode chi_squared automatic interection detection untuk klasifikasi uang jemput pada tradisi pernikahan di kecamatan pariaman utara - Ardatama, Rahul; helma, hema (UNIVERSITAS NEGERI PADANG, 2022)
One of the areas in Minangkabau which is famous for its marriage customs is Pariaman. Because there is a bajapuik tradition that requires a uang jemput for Ajo Piaman. According to the Head of the Nagari Customary Density in North Pariaman District, Ajo Piaman's uang jemput are certainly different and the factors that affect Ajo Piaman's uang jemput are employment, education, age, income, title, marriage, property, and year of marriage. The population of this study is partly Ajo Piaman and the sample is 100 Ajo piaman in North Pariaman District who are married. The purpose of this study was to determine the factors that affect Ajo Piaman's uang jemput and to find out the results of the classification of Ajo Piaman's uang jemput using CHAID analysis. The results of this study indicate that education, income and year of marriage factors affect uang jemput in North Pariaman District.